Chronic cerebrospinal venous insufficiency: does ultrasound really distinguish multiple sclerosis subjects from healthy controls? - UYSAL, ÖMER; Kantarci, Fatih; Albayram, Sait; Demirci, Nuri Onat; Esenkaya, Asim; Uluduz, Derya; Uysal, Omer; Saip, Sabahattin; Siva, Aksel (My University, 2012)
Objectives To investigate the differences between multiple sclerosis (MS) and control subjects by using extracranial venous grey-scale, colour and spectral Doppler ultrasound.